2014
DOI: 10.1186/s12989-014-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Short versus long silver nanowires: a comparison of in vivo pulmonary effects post instillation

Abstract: BackgroundSilver nanowires (Ag NWs) are increasingly being used to produce touchscreens for smart phones and computers. When applied in a thin film over a plastic substrate, Ag NWs create a transparent, highly-conductive network of fibers enabling the touch interface between consumers and their electronics. Large-scale application methods utilize techniques whereby Ag NW suspensions are deposited onto substrates via droplets. Aerosolized droplets increase risk of occupational Ag NW exposure. Currently, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 37 publications
3
60
0
Order By: Relevance
“…51 In the recent work by Silva et al , instillation of AgNWs in rats led to the deposition of AgNWs in the deep lungs. 9 Both AgNW lengths tested produced significant numbers of Ag-positive macrophages at Day 1. 9 Herein, sp-A/D induced agglomeration of the AgNW also within 24 hours, which could therefore be responsible for the high uptake of AgNWs by macrophages in the Silva study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…51 In the recent work by Silva et al , instillation of AgNWs in rats led to the deposition of AgNWs in the deep lungs. 9 Both AgNW lengths tested produced significant numbers of Ag-positive macrophages at Day 1. 9 Herein, sp-A/D induced agglomeration of the AgNW also within 24 hours, which could therefore be responsible for the high uptake of AgNWs by macrophages in the Silva study.…”
Section: Discussionmentioning
confidence: 94%
“…8 Recently, AgNWs were shown to produce dose-dependent inflammation in murine lungs and responses dependent on both AgNW length and dissolution rates. 9 The toxicity of AgNWs has not been thoroughly investigated and discrepancies still exist on the mechanism of biological action of AgNMs in general. 10, 11 The lack of consistency could be in part due to the fact that most studies have not considered the fate of AgNMs in biologically relevant environments and alterations to the physicochemical properties of as-synthesized NMs.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of inorganic particles is also known to induce MGC formation. MGC have been observed in the lungs of rodents after exposure to silica [115,116], asbestos [115,117], sepiolite nanoclay [116], silver nanowires [118], or multiwalled carbon nanotubes [119]. Giant cell interstitial pneumonitis is a pathological pattern of hard metal lung disease that is characterized by the presence of MGC [120,121].…”
Section: Interaction With Particulatesmentioning
confidence: 98%
“…There is a growing body of studies that describe MGC formation in response to particle inhalation. MGC are frequently [129] Crohn's disease and ulcerative colitis [130] Langerhans cell histiocytosis [131] Rheumatoid disease [132] Sarcoidosis [71] Vasculitides such as giant cell arteritis [133] Endogenous materials Keratin [134] Lipids [74] and cholesterol crystals [135] Monosodium urate crystals [136] Exogenous materials Engineered nanomaterials such as silver nanowires [118] and carbon nanotubes [119] Medical implants [137] Metals such as Al [138], Be [122], Zr [139], and Co/WC alloys [140] Minerals such as asbestos [141], silica [141], and talc [142] Plant materials [143] such as cactus spines, corn starch used with medical gloves, and wood splinters Infectionbacteria Brucellosis [144] Cat-scratch disease [145] Mycobacteria infection such as leprosy [146] and tuberculosis [106] Syphilis [147] Infection -fungus African histoplasmosis [148] Aspergillosis [149] Cryptococcosis [150] Infectionparasite Filariasis such as dirofilariasis [151] and onchocerciasis [152] Leishmaniasis [153] Schistosomiasis [154] observed in response to inhalation of antigens that cause hypersensitivity pneumonitis [113,114] and inhalation of other organic materials such as mycobacteria and fungi (Table 1.2). Inhalation of inorganic particles is also known to induce MGC formation.…”
Section: Interaction With Particulatesmentioning
confidence: 99%
“…In vivo studies are even more limited that in vitro ones; an in vivo toxicity study carried out by Silva et al evaluated the effect of AgNWs length on rats after intratecal instillation of a bolus dose [73]. They could not find a specific effect linked to length only, but they observed that both short (2 µm) and long (20 µm) AgNWs induced a dose-dependent foreign-body response.…”
Section: Toxicity Of Silver Nanowiresmentioning
confidence: 99%